Efektivitas Pembelajaran Online Pada Masa Pandemic Covid-19 Di Mts Negeri Kota Kupang - Siti ida Yanti; Ma'ruf Ishak Ola (Universitas Yudharta Pasuruan, 2021)
This research is motivated by learning conditions in the midst of the Covid-19 pandemic that must continue to run. Where teachers are required to provide learning that makes students understand and understand in accordance with the expected achievements. Therefore, along with the development of information and communication technology teachers are required to use online-based media with the aim of facilitating communication between teachers and students in the presenter of learning materials that can be accessed anytime and anywhere. The purpose of the study is to find out the effectiveness of online learning during the covid-19 pandemic in MTs Kota Kupang Academic Year 2021/2022. Use descriptive qualitative methods. The results showed that the effectiveness of online learning during the covid-19 pandemic carried out by teachers and students in Kupang City MTs was effective.